If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 4 = 15 Reorder the terms: 4 + 3b = 15 Solving 4 + 3b = 15 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3b = 15 + -4 Combine like terms: 4 + -4 = 0 0 + 3b = 15 + -4 3b = 15 + -4 Combine like terms: 15 + -4 = 11 3b = 11 Divide each side by '3'. b = 3.666666667 Simplifying b = 3.666666667
| 5x+10=3x+24 | | 11x+(-6x)+11= | | 9r-8=6r+7 | | (x^4+y^2)(x^4-y^2)= | | 3(x+4)-(-4)=2x+8-4 | | 5x^6+5x^5-40x^4+35x^3= | | 2x-x=1.5 | | 4x-10=2x+12 | | x^2=(x-2)*(x+6) | | 3t+9t=60 | | m=n+8 | | 3x+5=5x-9 | | 7u+11.59=32.31 | | 3x+7=6x-11 | | 19x^7-8x^5+16x^4= | | 2x=(x-2)*(x+6) | | -3(1+2v)=90 | | (x-3)(x-1)(2x-5)=6 | | 3(2x-10)=-12 | | 2x*21=28(x+5) | | (x-3)(x-1)(2x-5)=12 | | -4a-6+5a=-3 | | 6x^6-7x^4+17x^3= | | 2x^3-x^2-16x+15=0 | | (5r-4)(6r-6)= | | 7h+13=230 | | -6m-15=-3 | | 2y-1.7=3.3 | | Y=-x^2+x+6 | | -9(6+u)-20=-10 | | 9x^2-6x+1=4 | | y=z-18 |